Comparative Study Of Village Officials In Increasing Tourism Literacy And Creating Tourism Villages - Butarbutar, Augustinus Robin; Suhariyanto, Didik; Novaria, Rachmawati; Munizu, Musran (Journal Of Human And Education (JAHE), 2024)
When carrying out regular reporting, each servant reported a number of problems and potentials in Bengkol Mdura village, Bengkol Manado village, and Mekar Sari Jambi village which have a number of potentials to be developed into tourism villages with their own characteristics. The reult in this article show 1. Comparative studies have the main objectives, namely: 1. Comparing various groups or elements. 3. Identify common differences and similarities. 2. Data collection methods such as surveys, interviews, or secondary data analysis are used for various purposes, such as improving understanding, decision making, or hypothesis testing. 2. Tourism villages in the context of rural tourism are tourism assets based on rural potential with all its uniqueness and attractions which can be utilized and developed as a tourism product to attract tourist visits to the village location. 3. The author and teacher in this article believes that comparative studies are a solution for Bengkol Madura village, Bengkol Manado village, and Mekar Sari village in studying all aspects of tourist villages that have been recognized, have stable Village Original Income, and have been running for more from one year, in this case the villages of Tondano, Muaro Jambing, and Slopeng which became models for creating tourist villages.